ULTRASOUND-GUIDED LUMBAR PUNCTURE AS A DIAGNOSTIC AID TO IMPROVE PATIENT SAFETY AND SATISFACTION: DESIRABLE OR NECESSARY?. (29th November 2012) - Honarbakhsh, S; Osman, C; Teo, J; Gabriel, C
Abstract : Background: There is some evidence that using ultrasound (USS)-guidance reduces the number of lumbar puncture (LP) failures and improves the ease of the procedure in obese patients. We have begun to use this on our unit in unselected non-emergency patients and tested if it is associated with a reduced risk of complications and number of attempts required. Method: The study was designed as a mixed retrospective-prospective case-control design over a 6-month period. Retrospective data was collected from 28 patients that had a non-USS-guided LP. Prospective data was collected on 23 patients that underwent an USS-guided LP. Difficulty factors (DFs) such as scoliosis, obesity, previous spinal surgery or general immobility were recorded. Results: The mean attempt rate in patients without DFs was 1.6 with an unguided LP compared to 1.0 with USS-guided LP (p=0.02). In patients with DFs, this was 3.60 vs 1.67 (p=0.006). The back pain rate in patients without DFs was 13.3% without USS vs 0% with USS (n.s.). In patients with DFs this was 53.8% without USS and 8.3% with USS (p=0.017). A logistic regression analysis confirmed that US-guided LP was a good predictor. 14% of unguided LPs produced CSF samples which were blood contaminated. Discussion: This study demonstrates that USS-guided LPs are associated with reduced number of attempts, reduced complication rate and reduced blood contamination particularly in those with difficulty factors. USS-guided LP would aid clinicians in ensuring patient safety, reduction of post-procedure complications and better practice.